Phylotranscriptomic analysis and genome evolution of the Cypripedioideae (Orchidaceae). Issue 4 (2nd April 2018) - Unruh, Sarah A.; McKain, Michael R.; Lee, Yung‐I; Yukawa, Tomohisa; McCormick, Melissa K.; Shefferson, Richard P.; Smithson, Ann; Leebens‐Mack, James H.; Pires, J. Chris
Abstract : Premise of the Study: The slipper orchids (Cypripedioideae) are a morphologically distinct subfamily of Orchidaceae. They also have some of the largest genomes in the orchids, which may be due to polyploidy or some other mechanism of genome evolution. We generated 10 transcriptomes and incorporated existing RNA‐seq data to infer a multilocus nuclear phylogeny of the Cypripedioideae and to determine whether a whole‐genome duplication event (WGD) correlated with the large genome size of this subfamily. Knowing more about timing of ancient polyploidy events can help us understand the evolution of one of the most species‐rich plant families. Methods: Transcriptome data were used to identify low‐copy orthologous genes to infer a phylogeny of Orchidaceae and to identify paralogs to place any WGD events on the species tree. Key Results: Our transcriptome phylogeny confirmed relationships published in previous studies that used fewer markers but incorporated more taxa. We did not find a WGD event at the base of the slipper orchids; however, we did identify one on the Orchidaceae stem lineage. We also confirmed the presence of a previously identified WGD event deeper in the monocot phylogeny. Conclusions: Although WGD has played a role in the evolution of Orchidaceae, polyploidy does not appear to be responsible for the large genome size of slipper orchids. The conserved set of 775 largely single‐copy nuclear genes identified in this study should prove useful in future studies of orchid evolution.